Multi-Timescale Education Program for Temporal Expansion in Ecocentric Education: Using Fixed-Point Time-Lapse Images for Phenology Observation - Kazuhiko W. Nakamura; Akio Fujiwara; Hill Hiroki Kobayashi; Kaoru Saito (MDPI AG, 2019)
Ecocentric education programs should include a method for the in-depth understanding of multi-scale ecological time concepts. To accomplish this, the common restriction that ecocentric education should pertain only to realistic nature may have to be removed. The purpose of this research was to confirm the validity of a program featuring phenology observation, employing fixed-point time-lapse images as climate change learning, and to obtain suggestions on the influence of the program on the multi-timescale concepts of the learners. An observation sheet listing images of cherry flowering from 16 April to 15 March each year from 1996 to 2017 was created, and the 50-min educational program using the observation sheet was conducted with 189 third year junior high school students. The tendencies among students’ answers to the two questions before and after the program suggest that the program contributed to the students acquiring the hundreds-year timescale concept based on the short-term timescale concept of dynamic nature. The contribution of this research is to visualize long-term and multi-scale ecological time concepts. By combining long-term time-lapse images with everyday nature experiences, the possibility of expanding such emotions as wonder and attachment to nature towards a long-term ecological timescale is achieved.